Irritable Bowel Syndrome: Diagnosis and Treatment - Muhammad Syafiq; Marcellus Simadibrata K; Murdani Abdullah; E. Mujaddid (The Indonesian Society for Digestive Endoscopy, 2003)
Irritable bowel syndrome (IBS) is the most common functional disorder of the gastrointestinal tract. As a result of the lack of specific diagnostic testing and absence of circumscribed biology markers of the disease, its diagnosis is based on a myriad of symptoms. The term irritable bowel syndrome was probably first coined in 1944 by Peters and Bargen. In 1849, Cumming described the clinical manifestations of Irritable Bowel Syndrome. Irritable bowel syndrome is defined on the basis of the recently modified Rome criteria as the presence of at least 12 weeks (not necessarily consecutive) of abdominal discomfort or pain in the preceding 12 months that cannot be explained by structural or biochemical abnormalities, and that has at least two of the following three features: pain relieved with defecation, an onset associated with a change in the frequency of bowel movements (diarrhea or constipation), or an onset associated with a change in form of stool (loose, watery, or pellet-like). The syndrome can be divided into three subcategories according to the Modified Rome criteria II; those with a predominant symptom of diarrhea, constipation, or constipation alternating with diarrhea. There are several criteria for irritable bowel syndrome, one of which is the Manning criteria, applied in many epidemiological and clinical studies to identify irritable bowel syndrome. However, many investigators disagree with this criteria due to a seemingly poor validity in men. In an attempt to bring order to the specialty, consensus-based approach is adopted by a group of international experts, which led to the development of the Rome criteria for irritable bowel syndrome (Table 1). Extra-intestinal symptoms, including headache, backache, urinary and gynecologic symptoms, and fatigue, are more common in the constipation-predominant subgroup.